19 Manganese-enhanced T1 mapping for the detection of left ventricular remodelling and viability after myocardial infarction. (May 2019) - Spath, Nick; Dweck, Marc; Baker, Andrew; Newby, David; Semple, Scott
Abstract : Background: Delayed-enhancement magnetic resonance imaging (DEMRI) using gadolinium overestimates infarct size acutely and indirectly estimates myocardial viability by quantifying scar burden. Manganese, an essential trace element and paramagnetic calcium-analogue (administered as chelated manganese dipyridoxyl diphosphate, MnDPDP), defines myocardial viability directly by imaging functional calcium-handling mechanisms. Our previous preclinical work demonstrated manganese-enhanced MRI (MEMRI) has potential to detect altered calcium-handling in remodelling myocardium following infarction. Purpose: To assess whether MEMRI detects changes in myocardial calcium-handling after myocardial infarction (NCT03607669 ). Methods: Healthy volunteers (HV, n=20, 13 male, 42±11 years) and patients with acute ST-segment elevation myocardial infarction with reduced ejection fraction (n=8, recruitment ongoing) underwent dual DEMRI and MEMRI, ≥48 hours apart, with T1 mapping. Patients returned for repeat imaging at 3 months. Myocardial T1 was measured every 2.5 min for 40 min after intravenous MnDPDP (5 umol/kg) administration. Images were acquired at 3T (Siemens Magnetom Skyrafit) with T1 imaging performed with Shortened Modified Look-Locker Inversion recovery (WIP #1048 Siemens Healthcare Ltd). Scanner-generated T1 maps are analysed to quantify T1 within regions of interest. Results: No adverse effects were observed in any subject. In HV, MnDPDP rapidly reduced bloodpool T1 over 5 min (mean reduction 25.7%, 453±22 ms), followed by prompt normalisation to baseline by 40 min. Myocardial T1 also demonstrated a rapid initial descent (infusion phase) but this was followed by a slower, more gradual decrease which continued throughout the 40 min imaging period (mean reduction 25.2%, 283±9 ms) as evidence of Mn uptake by viable cardiomyocytes. In patients with acute myocardial infarction, the profile of myocardial T1 following MnDPDP was markedly different in the infarct compared to remote myocardium. In particular, areas of transmural infarction with microvascular obstruction demonstrated a recovery of T1 values similar to bloodpool (figure 1A), whilst T1 in regions of less extensive infarct plateaued after the infusion phase. In contrast to both, a sustained reduction was seen in the remote myocardium, similar to healthy volunteers. Three months post-myocardial infarction, two distinct T1 profiles were identifiable within the infarct zone (defined by DEMRI): (i) a central region demonstrating partial recovery of T1 following MnDPDP similar to microvascular obstruction and bloodpool, although less rapid, and (ii) the wider infarct region where T1 continued to decrease throughout the 40 min imaging period (figure 1B). This would suggest ongoing manganese uptake and viability despite near transmural late-enhancement (figure 1C), supported by improved wall thickening on cine imaging. Overall, T1 values at 40 min post-MnDPDP were 35.9% higher in regions of infarction compared to remote and healthy myocardium (1134±88 versus 843±28 ms, P<0.0001). All infarcts had T1 >1050 ms, whereas remote and healthy myocardium had T1 <950 ms. Conclusion: MEMRI of the myocardium with T1 mapping not only identifies myocardial infarction but also demarcates viability and delineates regions of viability within the infarct zone. This novel contrast imaging technique has exciting potential in ischaemic cardiomyopathy. Conflict of Interest: None